1991
DOI: 10.1021/jm00110a010
|View full text |Cite
|
Sign up to set email alerts
|

Topographically designed analogs of [cyclic] [D-Pen2,D-Pen5]enkephalin

Abstract: The conformationally restricted, cyclic disulfide-containing delta opioid receptor selective enkephalin analogue [D-Pen2,D-Pen5]enkephalin (1, DPDPE) was systematically modified topographically by addition of a methyl group at either the pro-S or pro-R position of the beta carbon of an L-Phe4 or D-Phe4 residue to give [(2S,3S)-beta-MePhe4]DPDPE (2), [(2R,3R)-beta-MePhe4]DPDPE (3), [(2S,3R)-beta-MePhe4]DPDPE (4), and [(2R,3S)-beta-MePhe4]DPDPE (5). The four corresponding isomers were prepared in which the beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 8 publications
(17 reference statements)
5
75
0
Order By: Relevance
“…The up to 5-fold difference in the gauche (+) population is unexpected since DPDPE and compound 1 have similar structures; both are 14-membered cyclic disulfides with aromatic residues at positions 1 and 4. Furthermore, a comparison against the potent (2S,3S)-isomer of [β-Me-p-NO 2 Phe 4 ]DPDPE with 10% gauche (+) population for Tyr, also can be made [22,45]. In this case, the increase in the gauche (+) may be a result of a substitution of a constrained aromatic residue at position 4.…”
Section: Compound 1 Has Unique Conformational Features As An Opioid Lmentioning
confidence: 99%
“…The up to 5-fold difference in the gauche (+) population is unexpected since DPDPE and compound 1 have similar structures; both are 14-membered cyclic disulfides with aromatic residues at positions 1 and 4. Furthermore, a comparison against the potent (2S,3S)-isomer of [β-Me-p-NO 2 Phe 4 ]DPDPE with 10% gauche (+) population for Tyr, also can be made [22,45]. In this case, the increase in the gauche (+) may be a result of a substitution of a constrained aromatic residue at position 4.…”
Section: Compound 1 Has Unique Conformational Features As An Opioid Lmentioning
confidence: 99%
“…First, the receptorligand interactions (structure-activity relationships) for these compounds have been well studied (1,2,(24)(25)(26)(27)30 f3-D-glucoside moiety, were chosen for further study to see whether analgesia (peptide transport) could be demonstrated in live mice.…”
mentioning
confidence: 99%
“…The free amino groups on the side chains of 5-aminovaleric acid, b-alanine, 4-aminobutyric acid, 6-aminohexanoic acid and p-aminobenzoic acid were protected before peptide synthesis with a Boc (N-tert-butoxycarbonyl) group as previously reported (11).…”
Section: Amine Protectionmentioning
confidence: 99%